Ninel Vasilyevna Deduh - «SISJP NAMS», Staff of SI (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The article is dedicated to the anniversary of the outstanding morphologist in the sphere of the locomotor system, Doctor of Biological Sciences, Professor Dedukh N.V.